Administrative Structure and Transportation Network in the Time of II. Abdulhamid in the Dersim Sanjak - Yilmazcelik, Ibrahim; Erdem, Sevim (Hale Sivgin, 2017)
Ottoman Empire had given importance to public Works and especially roads since its establishment. The roads built by the Ottoman, as in the Roman and Byzantine periods, were regarded not only as a way of conquering but also as a constant way policy, and financial benefits as well as military purposes were taken into consideration in the determination of the routes of the roads. The foundation of today's transportation network is more advanced than an older system composed of caravan roads and it is known to be so until at least 1920s. Military designed roads were old and static. Therefore, commercial caravan roads were more important than military roads in change of the road network. In Ottoman period while constructing military designed roads, if it was a new road network a walking instruction would be firstly prepared, if it was ready to use, transportation through the route would be enacted. Military designed roads were significant especially when padishah would set out. However, instead of military expedition, preventing banditry and guaranteeing the state security became important in construction of military designed roads in late periods of the Ottoman Empire. The Dersim Sanjak being located in dangerous conjunction point of the Eastern Anatolia and the Middle Eastern Anatolia was covered by Karasu in the west, Munzur mountain ranges in the North and Peri Su in the east. The geographical conditons of the district prevented the state from dominating in this district. This paper aims to examine transportation network in the district of Dersim where tribes would live in Ottoman period and its transportational connection with Mamuratul-aziz, Erzurum Province, Van Province and Diyarbekir Province surrounding Dersim, as well.
Keywords: Dersim; Sanjak; Ottoman; Transportation; Abdulhamid II